Regional Health Care Decentralization in Unitary States: Equal Spending, Equal Satisfaction? - Joan Costa-Font; Gilberto Turati (London School of Economics and Political Science (LSE), European Institute, 2016)
Does regional decentralization threaten the commitment to regional equality in government outcomes? We attempt to shed light on this question by drawing on unique evidence from the largest European unitary states to have engaged in countrywide health system decentralization: Italy and Spain. We estimate, decompose, and run counterfactual analysis of regional inequality in government output (health expenditure per capita) and outcome (health system satisfaction) during expansion of health care decentralization in both countries. We find no evidence of increase in regional inequalities in outcomes and outputs in the examined period. Inequalities are accounted for by differences in health system design.
Keywords: H7; I18; I3; 330; health care decentralization; regional inequality; health care; Oaxaca decomposition